2000
DOI: 10.1016/s0168-0102(00)00137-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of tributyltin in rat hippocampal slice cultures

Abstract: The neurotoxic effects of tributyltin (TBT), an endocrine-disrupting chemical, were evaluated in organotypic slice cultures of immature rat hippocampus. Confocal microscopy study with propidium iodide showed that TBT induced severe neuronal death in a concentration-and time-dependent manner with CA3 \ CA1\ dentate gyrus ranking of vulnerability of the hippocampal subfields. Dead or damaged neurons exhibited chromatin condensation, which is one of the morphological characteristics of apoptosis, as revealed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
3
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 46 publications
3
29
3
3
Order By: Relevance
“…4) , 2005); its expression in adult brain cells may therefore sensitise them to certain apoptotic stimuli. An examination of the cells that express Bim in the adult brain may provide an insight into Bim's role in the adult cerebrum, particularly in the CA3, which has been shown to be especially sensitive to brain trauma, protein hyperphosphorylation and endocrine-disruption, (Mizuhashi et al, 2000, Runden et al, 1998, Tashlykov et al, 2007.…”
mentioning
confidence: 99%
“…4) , 2005); its expression in adult brain cells may therefore sensitise them to certain apoptotic stimuli. An examination of the cells that express Bim in the adult brain may provide an insight into Bim's role in the adult cerebrum, particularly in the CA3, which has been shown to be especially sensitive to brain trauma, protein hyperphosphorylation and endocrine-disruption, (Mizuhashi et al, 2000, Runden et al, 1998, Tashlykov et al, 2007.…”
mentioning
confidence: 99%
“…We further found in our current study that TBT induces ER stress-associated apoptosis in cultured PC12 cells by upregulating the Bcl-2 family protein Bim (Figure 4(c)). It has been found previously that TBT induces an excessive increase in Ca 2+ and apoptotic cell death in some types of neuronal cells [12,[62][63][64]. It was also suggested in another report that TBT mobilizes intracellular Ca 2+ in PC12 cells by enhancing the transmembrane influxes of Ca 2+ [65].…”
Section: Discussionmentioning
confidence: 80%
“…On the contrary, we observed a dose and time dependant reduction of the inward Ca ++ and Na + currents. Many previous reports have also demonstrated that TBT increases intracellular Ca ++ concentration (Oyama et al 1994;Mizuhashi et al 2000;Nakatsu et al 2006Nakatsu et al , 2007, which, in turn, can induce apoptosis (Chow et al 1992;Corsini et al 1997;Stridh et al 1999). Apoptosis is related to mitochondrion dysfunction, demonstrated by the MTT assay, inducing ATP depletion and Ca ++ release.…”
Section: Discussionmentioning
confidence: 94%